Communication Is Key: Mechanisms of Intercellular Signaling in Vasodilation. Issue 5 (May 2017) - Freed, Julie K.; Gutterman, David D.
Abstract : Abstract: Thirty years ago, Robert F. Furchgott concluded that nitric oxide, a compound traditionally known to be a toxic component of fuel exhaust, is in fact released from the endothelium, and in a paracrine fashion, induces relaxation of underlying vascular smooth muscle resulting in vasodilation. This discovery has helped pave the way for a more thorough understanding of vascular intercellular and intracellular communication that supports the process of regulating regional perfusion to match the local tissue oxygen demand. Vasoregulation is controlled not only by endothelial release of a diverse class of vasoactive compounds such as nitric oxide, arachidonic acid metabolites, and reactive oxygen species, but also by physical forces on the vascular wall and through electrotonic conduction through gap junctions. Although the endothelium is a critical source of vasoactive compounds, paracrine mediators can also be released from surrounding parenchyma such as perivascular fat, myocardium, and cells in the arterial adventitia to exert either local or remote vasomotor effects. The focus of this review will highlight the various means by which intercellular communication contributes to mechanisms of vasodilation. Paracrine signaling and parenchymal influences will be reviewed as well as regional vessel communication through gap junctions, connexons, and myoendothelial feedback. More recent modes of communication such as vesicular and microRNA signaling will also be discussed.